2010
DOI: 10.1051/forest/2009096
|View full text |Cite
|
Sign up to set email alerts
|

Do artificial and natural defoliation have similar effects on physiology of Eucalyptus globulus Labill. seedlings?

Abstract: Abstract• Artificial defoliation is often used to simulate defoliation by herbivory and is usually considered a good indication of a plant's response to a given type of damage. However, the findings of studies directly comparing the two defoliation types are inconsistent.• Here, the short term effects of artificial and insect defoliation by larvae of Paropsisterna agricola on growth, biomass allocation and photosynthetic capacity of Eucalyptus globulus seedlings were compared in a glasshouse experiment. The ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 38 publications
3
34
1
2
Order By: Relevance
“…The study carried out was designed to fit within these constraints and as a consequence limited the number of trees. Overall, four-year-old E. globulus were able to compensate for the partial defoliation in a similar way as younger E. globulus (Eyles et al, 2009;Quentin et al, 2010). Our results also suggest that the full impact of 45% leaf area removal on growth and resource allocation had been fully tolerated after 11 months recovery time, likely via activation of a number of physiological compensatory mechanisms which include: increase photosynthetic rate, improvement of tree's water relation and utilisation of carbon assimilates.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The study carried out was designed to fit within these constraints and as a consequence limited the number of trees. Overall, four-year-old E. globulus were able to compensate for the partial defoliation in a similar way as younger E. globulus (Eyles et al, 2009;Quentin et al, 2010). Our results also suggest that the full impact of 45% leaf area removal on growth and resource allocation had been fully tolerated after 11 months recovery time, likely via activation of a number of physiological compensatory mechanisms which include: increase photosynthetic rate, improvement of tree's water relation and utilisation of carbon assimilates.…”
Section: Resultssupporting
confidence: 58%
“…While artificial defoliation studies do not accurately mimic what occurs in the real world (e.g. Quentin et al, 2010), they can provide a sounder basis for understanding the effects of insect defoliation that can then be used to develop management strategies. We established a field experiment to examine the morphological and eco-physiological effects of artificial defoliation (45% leaf removal) on the growth and biomass allocation in 4-year-old, closed canopy stand of E. globulus trees.…”
Section: Introductionmentioning
confidence: 99%
“…Douglas fir under defoliation treatments had the significant decreases in height and diameter growth [37], while artificial defoliation of Eucalyptus globulus only negatively affected the diameter growth [38]. Our results showed that there were significant differences in height growth of P. deltoides males and females when exposed to defoliation.…”
Section: Discussionmentioning
confidence: 57%
“…Sin embargo, Collett y Neumann (2002) efectuaron artificialmente distintos niveles de defoliación, encontrando que sólo el 100% redujo significativamente la altura y el diámetro basal del tallo de plantas de E. globulus durante la implantación, mientras que la defolición parcial no influyó sobre el crecimiento e incluso la remoción de las hojas inferiores favoreció el aumento de altura.En este trabajo la defoliación observada nunca alcanzó el 100% de las hojas (datos no presentados) y, sin embargo, las plantas con herbivoría redujeron, con respecto a las plantas control, en promedio un 10,3 % y un 26,5 % el diámetro final y el crecimiento en altura, respectivamente. Esto podría explicarse a través de las observaciones realizadas por Quentin et al (2010), quienes encontraron que la defoliación producidapor insectos en plantines de E. globulusde similar edad que los utilizados en este ensayo, redujo significativamente su altura y diámetro, mientras que la artificial sólo afectó el diámetro, concluyendo que las defoliaciones simuladas podrían subestimar el efecto de la herbivoría.…”
Section: Figura 1 -Número De Folhas Por Planta (Média ± Ep) De Difereunclassified
“…El distinto comportamiento de las plantas frente a la herbivoría podría ser una característica asociada al genotipo de cada procedencia. Se ha observado que las plantas de E. globulus sometidas a defoliación natural y artificial, aumentan la capacidad fotosintética del follaje remanente y modifican la partición de los asimilados (PIKARD et al, 2007;QUENTIN et al, 2010). Como en este trabajo todos los brotes axilares fueron removidos en cada observación, el principal órgano destino de los fotoasimilados fue el brote apical, cuyo desarrollo favorece el crecimiento en altura y la emisión de nuevas hojas, aumentando el área foliar.…”
Section: Figura 1 -Número De Folhas Por Planta (Média ± Ep) De Difereunclassified